Geschriebener Dialekt in Südtiroler Facebook-Texten - Glück, Alexander; Glatznieks, Aivars (Linguistik Online, 2019)
This case study deals with the reflexes of unaccentuated, word-final Standard German -er in multisyllabic words, attested in German Facebook texts written by South Tyrolean Facebook users with German as (one of) their first language(s). After preliminary considerations for the analysis of written language and a presentation of the corpus, linguistic data will be related to metadata on texts and users, taking spatial, social and situational criteria into account, in this way assigning particular variants to particular varieties.